Implementasi Metode Dynamic Time Warping Pada Aplikasi Kamus Bahasa Isyarat Indonesia Sebagai Media Komunikasi - Amalia Daulay, Rizki; Ikhsan, Muhammad; Halim Hasugian, Abdul (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2023)
Communication is something vital in human existence. Communication is generally divided into two, namely verbal and non-verbal. For deaf and speech impaired people, the comic used is sign language and the intermediary used is a web-based application based on sign language from SIBI, with the implementation of the Dynamic Time Warping (DTW) method to analyze its usability and use. The use of this method in sign language dictionaries is to change the time coefficient into distance, because similarities in images can produce patterns from the object that is the example. In this test there are 24 letters and for each letter 10 image models taken via camera are used, and training is carried out with 50 datasets. The average test result collected reaches 90% because the condition of the hand can be said to be like the condition of other hands. This application is used to learn SIBI language, translate and read hand movements via real-time video. And during testing, accuracy results affect certain situations such as camera capacity, model coloring in the background and hand movements, and light brightness in the training data. Keyword: Metode Dynamic Time Warping, Indonesian Sign Language System, Deaf and Speech Impaired